From Redistribution to Social Justice: A PRISMA-Based Systematic Review of Islamic Social Finance and Welfare Outcomes in Developing Countries - Ekawaty, Marlina; Hanafiansyah, Mochammad Rizki (Side: Scientific Development Journal, 2026)
Islamic economics emphasizes social justice and equitable welfare distribution as core normative objectives, particularly through zakat, waqf, and Islamic social finance instruments. However, empirical findings on their effectiveness remain fragmented across institutional, social, and governance contexts. This study aims to systematically examine the role of Islamic social finance in promoting social justice, redistribution, and welfare. This research adopts a Systematic Journal Review approach by synthesizing peer-reviewed qualitative and quantitative studies published in reputable national and international journals. Articles were selected based on relevance, methodological rigor, and empirical focus on Islamic social finance and welfare outcomes. The findings indicate that zakat, waqf, and related instruments significantly contribute to poverty alleviation, welfare improvement, and economic empowerment. Quantitative evidence confirms statistically significant relationships between Islamic social finance distribution and welfare indicators, although governance constraints may weaken direct impacts in certain contexts. Qualitative studies highlight the importance of institutional accountability, digital integration, and productive financing models in enhancing redistributive effectiveness. In conclusion, Islamic social finance constitutes a viable and multidimensional mechanism for advancing social justice and welfare, provided it is supported by robust governance and strategic institutional integration.